"I Have Failed Them and Failed My Duties": Experiences of Hospital Social Workers Discharging Patients into Homelessness. Issue 1 (15th December 2021) - Morris, Rae; Lewis, Fiona; Baker, Nancy; Saul, Megan; Bohachewski, Kym
Abstract: Homelessness is a long-standing issue at the forefront of healthcare globally, and discharge of homeless patients from hospital settings can exacerbate gaps and burdens in healthcare systems. In hospitals, social workers often take on the majority of responsibility for facilitating patient discharge transitions out of hospital care. Research in this area to date has explored experiences and outcomes of homeless clients, and the experiences of social workers in these roles are not well known. The current study's objective was to elucidate observations and experiences of hospital social workers who discharge patients into homelessness. A total of 112 social workers responded to an online questionnaire, and responses to open-ended questions were analyzed for thematic content. Four overarching themes emerged: (1) complexity of clients, (2) systemic barriers, (3) resource gaps, and (4) negative impact on social workers. It is clear that significant change is required to address the multitude of challenges that intersect to reinforce health inequities. Results can be used by social workers, health authorities, community providers, researchers, and policymakers in discussions about best practices for homeless clients.